Fibromuscular dysplasia of the coronary arteries: a rare cause of death in infants and young children - Mogler, Carolin; Springer, Wolfgang; Gorenflo, Matthias (Cardiology in the young, 2016)
Fibromuscular dysplasia is a common vascular disease, which mainly affects the renal arteries. In this study, we report the case of a 1-day-old infant who presented with severe left ventricular dysfunction immediately after birth, and subsequently died 3 days postnatally. At autopsy, an extensive myocardial infarction of the left ventricle and the septum was found, caused by an isolated fibromuscular dysplasia of left coronary artery.